Enhanced dielectric properties in Ba0.85Ca0.15Zr0.10Ti0.90O3/La0.67Ca0.33MnO3 laminated composite. (February 2018) - Li, S.B.; Wang, C.B.; Shen, Q.; Zhang, L.M.
Abstract: We report the microstructure, dielectric, ferroelectric and magnetoelectric properties of Ba0.85 Ca0.15 Zr0.10 Ti0.90 O3 /La0.67 Ca0.33 MnO3 (BCZT/LCMO) laminated composite prepared by Plasma Activated Sintering. A perfect bonding BCZT/LCMO interface without structural defects was demonstrated by SEM and TEM analysis. The remnant polarization, coercive electric field and ME coefficient of the composite were 10.1 μC/cm 2, 1.97 kV/cm and 2.65 mV/cm·Oe, respectively. Enhanced dielectric properties (Room-temperature εr  = 7217, εm  = 25, 097, at 1 kHz) were achieved for the laminated composite, as explained by the contribution of ferromagnetic LCMO and Maxwell-Wagner model. Graphical abstract: